The Radiographic Anatomy of the Gastrointestinal Tract of the Lesser Mousedeer (Tragulus javanicus) - Richardson, K. C.; Vidyadaran, M. K.; Azmi, T. I.; Fuzina, N. H. (1988)
The radiographic anatomy of the Lesser Mousedeer (Tragulus javanicus) is described. The mousedeer has an extremely large stomach complex which fills the left and the ventral right of the abdomen. No omasum or caudodorsal blind sac were found. The reticulum usually lay cranioventrally on the left side abutting the diaphragm. The abomasal fundus lay caudal and ventral to the reticulum. The rate of passage of radiopaque substances along the alimentary tract is given. Faeces was first noted to form in the spiral colon. Small particles and fluid passed rapidly through the alimentary tract Ix =44.5 hr). Particles with densities approaching that of straw remained in the rumen whilst heavy metals were retained in the reticulum.